2014
DOI: 10.4172/2157-7110.1000335
|View full text |Cite
|
Sign up to set email alerts
|

Verification of Meso-Zeaxanthin in Fish

Abstract: Background/ObjectivesThe carotenoids lutein (L), zeaxanthin (Z), and meso-zeaxanthin (MZ) accumulate in the central retina (the macula), where they are collectively known as macular pigment (MP). MP has been shown to enhance visual function in both diseased and non-diseased retinae, and therefore an understanding and confirmation of, the origins of these carotenoids is needed. Studies have shown that L and Z are present in many foodstuffs found in a typical Western diet (e.g. spinach, kale, peppers, yellow cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…meso -Zeaxanthin is rarely found in the human diet, but it has been detected in shrimp carapace, fish skin, and turtle fat, where all three isomers of zeaxanthin were found (Maoka et al, 1986), and Nolan's group has recently confirmed its presence in fish skin using more modern methods (Nolan et al, 2014; Thurnham et al, 2015). A significant amount of meso -zeaxanthin has been detected in commercially produced chicken eggs in Mexico where it is commonly added to the feed to achieve desirable coloration (Wang et al, 2007).…”
Section: Basic Science Of the Macular Pigment Carotenoidsmentioning
confidence: 99%
“…meso -Zeaxanthin is rarely found in the human diet, but it has been detected in shrimp carapace, fish skin, and turtle fat, where all three isomers of zeaxanthin were found (Maoka et al, 1986), and Nolan's group has recently confirmed its presence in fish skin using more modern methods (Nolan et al, 2014; Thurnham et al, 2015). A significant amount of meso -zeaxanthin has been detected in commercially produced chicken eggs in Mexico where it is commonly added to the feed to achieve desirable coloration (Wang et al, 2007).…”
Section: Basic Science Of the Macular Pigment Carotenoidsmentioning
confidence: 99%
“…The macula is located roughly in the center of the retina and is responsible for detailed central vision. The yellow coloration of the macula is due to the presence of the macular pigment (MP) in the axons of its photoreceptors [1] which is composed of lutein, zeaxanthin-major carotenoids in the human diet (mainly from fruits and vegetables)-and meso-zeaxanthin, which is believed to be obtained from the dietary lutein in the retina and, in small amounts, from the diet [2]. These carotenoids are found at the macula in higher concentrations than anywhere else in the body.…”
Section: Introductionmentioning
confidence: 99%
“…This is a unique phenomenon in nature, especially since vertebrates normally obtain carotenoids through their diet and are incapable of producing these molecules de novo (2,3). meso-zeaxanthin is not commonly found in dietary sources; besides the eyes of vertebrates, this carotenoid is present in shrimp shells, turtle fat, and fish skin (2,4,5). Hundreds of carotenoids are present in nature, and even though primates consume more than 50 of them, meso-zeaxanthin is one of only three carotenoids present in the foveal center of the retina, the region responsible for sharp, central vision.…”
mentioning
confidence: 99%